2019
DOI: 10.1186/s13018-019-1499-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of percutaneous kyphoplasty combined with anti-osteoporosis drug on postmenopausal women with osteoporotic vertebral compression fracture and analysis of postoperative bone cement leakage risk factors: a retrospective cohort study

Abstract: BackgroundThe purpose of this study is to explore the therapeutic effect of percutaneous kyphoplasty (PKP) combined with anti-osteoporosis drug, zoledronic acid, on postmenopausal women with osteoporotic vertebral compression fracture (OVCF) and to perform an analysis of postoperative bone cement leakage risk factors.MethodsA total of 112 OVCF patients, according to therapeutic regimens, were divided into control group (n = 52, treated with PKP) and observation group (n = 60, treated with PKP and zoledronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
10
15
0
Order By: Relevance
“…We found that the rates of vertebral compression and kyphosis correction in the two groups gradually decreased significantly with time, suggesting that vertebral height and kyphosis angle gradually lost after surgery, which was consistent with previous findings [7,14]. In the treatment of OVCF without IVC by PVP and PKP, the injected bone cement of the former is mainly embedded in cancellous bone, while the bone cement of the latter is mainly filled with clumps, so stress occlusion is more likely to occur after PKP and lead to recollapse [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the rates of vertebral compression and kyphosis correction in the two groups gradually decreased significantly with time, suggesting that vertebral height and kyphosis angle gradually lost after surgery, which was consistent with previous findings [7,14]. In the treatment of OVCF without IVC by PVP and PKP, the injected bone cement of the former is mainly embedded in cancellous bone, while the bone cement of the latter is mainly filled with clumps, so stress occlusion is more likely to occur after PKP and lead to recollapse [32].…”
Section: Discussionsupporting
confidence: 92%
“…Since 1984, Galiber et al [12] applied PVP in the treatment of 1 case of C 2 vertebra invasive hemangioma to find its advantages of simple operation and definite effect. PVP and PKP have gradually become one of the effective methods to treat vertebral tumor and OVCF [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the rates of vertebral compression and kyphosis correction in the two groups gradually decreased significantly with time, suggesting that vertebral height and kyphosis angle gradually lost after surgery, which was consistent with previous findings [7,14]. In the treatment of OVCF without IVC by PVP and PKP, the injected bone cement of the former is mainly embedded in cancellous bone, while the bone cement of the latter is mainly filled with clumps, so stress occlusion is more likely to occur after PKP and lead to recollapse [33].…”
Section: Discussionsupporting
confidence: 92%
“…Since 1984, Galiber et al [12] applied PVP in the treatment of 1 case of C 2 vertebra invasive hemangioma to find its advantages of simple operation and definite effect. PVP and PKP have gradually become one of the effective methods to treat vertebral tumor and OVCF [8,13,14]. Kümmell's disease is a rare type in OVCF after minor trauma, which is progressive occurrence of vertebral collapse and kyphosis due to vertebral ischemia and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The correction rates of vertebral compression rate and kyphosis both in the two groups gradually lost with time, which was consistent with previous ndings [30,31]. In the vertebral intensive treatment of OVCFs, bone cement in the PVP group was mainly embedded in cancellous bone, while bone cement in the PKP group was mainly distributed in clumps, so stress blocking is more likely to occur after PKP surgery, resulting in recollapse [32].…”
Section: Resultssupporting
confidence: 89%